A relação entre imaginário e engajamento na fenomenologia de J. P. Sartre - Salamoni, Eduardo Simionato (2022)
This work aims to analyze the relationship between the imaginary and the engagement present in Jean-Paul Sartre's phenomenology. For this we will begin by elucidating what the imagining consciousness is and what is its way of relating to objects. Unlike the philosophical tradition, Sartre understands that the image is not a mental object or a mental representation, but that the image is a way that consciousness has to relate to objects in the real world. However, this mode differs from that of perception, where we observe objects, in imagination we almost observe objects, because they appear as if they were observable, but all their content was constituted by consciousness, there is nothing to learn from it. Every product of the imaginary is an unreal, an object that does not have the basic characteristics to be real, and that appears to consciousness from its absence or inexistence. Then the imagining consciousness can take a step back from the world to constitute the unreal object, so the imaginary is negation of the world and escape from being-in-the-world. However, Sartre asserts that writers must be engaged, at least those who write prose. We will then see how literature, as a product of the imaginary, is denial of the world, escape, and also the only possible place for engagement to be carried out in its entirety. Literature has an ambiguity that is part of its structure, being composed of words, it is at the same time an unreal and an act of unveiling and communication. This is because the aesthetic object that is the literary work only exists as long as it is sustained by a concrete act of the imagining consciousness called reading. Reading enables an encounter and recognition of freedoms, of the writer and the public, in addition to being able to bring what was written to the reflective plane. Therefore, we will show, from a thorough analysis of Sartre's works on these subjects, how prose can, at the same time, be unreal and be engaged.